The Relationship between Mother's Knowledge and Monitoring of Toddler Nutritional Status at Posyandu Pulo U Village, Tanah Luas District, North Aceh Regency - Dedy Ahmady; Chairannur Dara Phonna (Jurnal Kesehatan Akimal, 2022)
The prevalence of children under five with weight below the red line is total 526 children (0.9%), who were malnourished 1005 children (5.45%) in 2020. This study aims to identify the knowledge relationship mothers with nutritional monitoring toddler in Integrated Healthcare Center Village Pulo U District Land Area, North Aceh. This research is in the form of descriptive correlative with cross-sectional design, carried out in Pulo U Village, District Tanah Luas from October 11, 2021 to January 31, 2022 with a sample of 37 mothers. Data was collected through interview and distributing questionnaire. An Univariate-and-bivariate data analysis used the chi-square test. From the univariate test, it is known that knowledge mother about the majority of nutrition is in the good category, namely 15 respondents (40.5%), enough category 14 respondents (37.8%) and knowledge in the less category 8 respondents (21.6%). The distribution of the frequency of monitoring the nutrition of children under five is in the good category, as many as 30 respondents (81.1%), while those who are lacking in monitoring the nutrition of children under five to the Posyandu are 7 respondents (18.9%). p-value-0.014 <0.05, meaning that there is a significant relationship between the knowledge possessed by the mother and the monitoring of nutritional status toddlers to the Posyandu in the Village Pulo U Sub-district, Land Area District North Aceh. It is recommended to mothers who have toddlers to always monitor their toddler's nutrition to the Posyandu.